2020
DOI: 10.3390/biom10040502
|View full text |Cite
|
Sign up to set email alerts
|

Luteolin-7-O-Glucoside Inhibits Oral Cancer Cell Migration and Invasion by Regulating Matrix Metalloproteinase-2 Expression and Extracellular Signal-Regulated Kinase Pathway

Abstract: Oral squamous cell carcinoma is the sixth most common type of cancer globally, which is associated with high rates of cancer-related deaths. Metastasis to distant organs is the main reason behind worst prognostic outcome of oral cancer. In the present study, we aimed at evaluating the effects of a natural plant flavonoid, luteolin-7-O-glucoside, on oral cancer cell migration and invasion. The study findings showed that in addition to preventing cell proliferation, luteolin-7-O-glucoside caused a significant re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 53 publications
0
20
0
Order By: Relevance
“…It was widely demonstrated that the development of OSCC was strictly influenced by unhealthy habits such as alcohol abuse, tobacco, tobacco-derivate, chewing betel nut ( Ng et al, 2017 ; Falzone et al, 2019 ), and human papillomavirus (HPV) infection ( Chi et al, 2015 ). OSCC was generally asymptomatic in the early stages, which can lead to late diagnosis, extensive lesions, and potential metastases, while lymph node metastases were widely recognized as a major cause of poor survival ( Gharat et al, 2016 ; Bray et al, 2018 ; Velmurugan et al, 2020 ). The 5-year survival for OSCC has been reported approximately 50% ( Warnakulasuriya, 2009 ; Taghavi and Yazdi, 2015 ; Stanciu et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…It was widely demonstrated that the development of OSCC was strictly influenced by unhealthy habits such as alcohol abuse, tobacco, tobacco-derivate, chewing betel nut ( Ng et al, 2017 ; Falzone et al, 2019 ), and human papillomavirus (HPV) infection ( Chi et al, 2015 ). OSCC was generally asymptomatic in the early stages, which can lead to late diagnosis, extensive lesions, and potential metastases, while lymph node metastases were widely recognized as a major cause of poor survival ( Gharat et al, 2016 ; Bray et al, 2018 ; Velmurugan et al, 2020 ). The 5-year survival for OSCC has been reported approximately 50% ( Warnakulasuriya, 2009 ; Taghavi and Yazdi, 2015 ; Stanciu et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Perdomo and collaborators described the important role of myricitrin in inhibiting the proliferation and transformation of carcinogenic cells, as well as its chemopreventive effects 44 . In addition, Luteolin‐7‐O‐glucoside, a common compound present in both extracts, was considered as very promising multi‐target flavonoid and it was widely applied in anticancer therapies 45 . Several studies have potentiated its antineoplastic effects, which were mostly associated with increased cancer cell death and promised apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have potentiated its antineoplastic effects, which were mostly associated with increased cancer cell death and promised apoptosis. In fact, it was reported that this flavonoid exhibited antitumoral effects on Human oral squamous carcinoma cell lines, 45 on human colon adenocarcinoma cancer cell line, 46 and on human liver cancer by inducing apoptosis 47 . Furthermore, phenolic compounds identified in EARE such as polydatin, trans‐hydroxycinnamic acid, and hyperoside have been also described as antioxidant, anti‐inflammatory, and potential agent against cancer 48‐50 …”
Section: Discussionmentioning
confidence: 99%
“…In this regard, compounds of natural origin have yielded promising results as well. For instance, a natural flavonoid, luteolin-7-O-glucoside, has been reported to inhibit migration and invasion in oral cancer cells through regulating MMP-2 expression (Velmurugan et al 2020). Another dietary flavonoid, myricetin, has inhibited migration of A549 lung cancer cells via downregulating MMP-2 and -9 expression (Kang et al 2020).…”
Section: Discussionmentioning
confidence: 99%